Characteristics of discharge in crossed ЕxН fields near breakdown curve in acceleration and plasma regime - Jamirzoev, A.; Yakovin, S.; Zykov, A. (Вопросы атомной науки и техники, 2013)
In the present study the characteristics of discharge in crossed EH fields in acceleration and plasma regimes have been researched at low voltages near the breakdown curve. The new experimental data for current-voltage characteristic and their dependence on argon pressure and magnetic fields strength are presented. It is shown that initial stage of the current-voltage characteristic in acceleration and plasma regime are quite similar and correspond to regime with “oscillating” electrons. The theoretic model based on the energy balance of electrons in plasma regime is presented as well as the comparison of the theory with the experiment. The obtained results may be useful for further development of magnetron sputtering systems and plasma accelerators with closed electrons drift.